The Cytotoxicity Effect of Pyocyanin on Human Hepatocellular Carcinoma Cell Line (HepG2) - Mohammed, Hind; Yossef, Hanaa; Mohammad, Farooq (Iraqi Journal of Science, 2023)
Ninety eight specimens were collected from patients referring different hospitals in Baghdad in period from August to November in 2012. Specimens including (swabs from (Sputum, burn, wound, urine, ear, and eye).Sixty six isolates were identified as Pseudomonas aeruginosa. The isolates were identified according to morphological, cultural, biochemical characteristics and API 20E test. 90% of P. aeruginosa isolates produced pyocyanin pigment on King A medium in different amounts, whereas other isolates were produced other types of pigments such as (pyoverdine-yellow, pyorubin-red, and pyomelanin-black) on King B medium and also in different amounts.Quantitative assay of pyocyanin production was conducted. The results were shown that the isolate of sputum from cystic fibrosis (CF) was greatest in production of pyocyanin. Pyocyanin purified and thier cytotoxicity effect on HepG2 cell line were studied in vitro. The results were shown that pyocyanin has cytotoxic effect on HepG2 cell line caused inhibition in growth of the cell line, the inhibition rate ranged from 7% to 84%.